2008
DOI: 10.1007/s11605-008-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Reflux Monitoring in the Acute Gastroesophageal Reflux Porcine Model Using Esophageal Multichannel Intraluminal Impedance Measurement

Abstract: MII improves the detection of reflux in the acute reflux porcine model. The finding that after sole mobilization of the esophagus the intragastric pressure needed to provoke reflux was increased although the finding that the pressure of the lower esophageal sphincter was decreased needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…An extensive review of the literature showed that there are only a few animal models for studying GER (rats, dogs, cats, pigs) [8,18]. Most of these models were specifically designed to characterize GER in non-physiological conditions and during short-term measurements (mostly < 1 hour) [8,19]. In addition, there are no animal models of GER in newborns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive review of the literature showed that there are only a few animal models for studying GER (rats, dogs, cats, pigs) [8,18]. Most of these models were specifically designed to characterize GER in non-physiological conditions and during short-term measurements (mostly < 1 hour) [8,19]. In addition, there are no animal models of GER in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of the literature reveals that there are only a few published animal models for studying GER (rats, dogs, cats, pigs) mostly in nonphysiological conditions and during shortterm measurements (mostly < 1 hour) (10)(11)(12)). An exception is the adult rat, which has been used for studying the consequences of chronic reflux related lung aspirations (13).…”
Section: Discussionmentioning
confidence: 99%
“…This was, based on the hypothesis that lengthening of the intra-abdominal part of the esophagus improves lower esophageal sphincter (LES) function and, consequentially, resolves gastroesophageal reflux. 6,7 This hypothesis has been supported by experimental findings 8 and meticulous considerations on the physiology of the LES by Stelzner et al As a consequence of their research, they postulated a stretch closure mechanism of the LES, which improves after isometric distention of the spiral esophageal muscular fibers. [9][10][11] Initial results of cardiophrenicopexy procedures were promising as reflux control was achieved in up to 90% of patients.…”
mentioning
confidence: 86%
“…After endotracheal intubation, the animals were anesthetized with isoflurane and N 2 O [27]. No muscle relaxation was performed [28]. After surgical exposure, the right internal jugular vein was punctured and a 4F central venous catheter introduced.…”
Section: Animalsmentioning
confidence: 99%